2005
DOI: 10.1111/j.1523-1755.2005.00271.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized LDL activates PAI-1 transcription through autocrine activation of TGF-β signaling in mesangial cells

Abstract: These results suggest that Ox-LDL activates TGF-beta/Smad signaling to stimulate PAI-1 transcription in human mesangial cells. Thus, progression of glomerular disease may be promoted by PAI-1 up-regulation in human mesangial cells mediated by the Ox-LDL-induced TGF-beta/Smad signaling pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 36 publications
2
31
0
1
Order By: Relevance
“…PAI-1 may also play a critical role in the development of agingassociated pathological changes associated with CAD (Yamamoto et al 2014). Early work has indicated that PAI-1 can be upregulated through oxidative stress (Vulin and Stanley 2004) and inflammation (Alessi and Juhan-Vague 2004;Song et al 2005). Hence, significant inhibition of PAI-1 by F105 supplementation would be of benefit in attenuating the deterioration of vessels particularly in a subset of subjects with initial HbA1c > 5.4 and one additional cardiometabolic risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…PAI-1 may also play a critical role in the development of agingassociated pathological changes associated with CAD (Yamamoto et al 2014). Early work has indicated that PAI-1 can be upregulated through oxidative stress (Vulin and Stanley 2004) and inflammation (Alessi and Juhan-Vague 2004;Song et al 2005). Hence, significant inhibition of PAI-1 by F105 supplementation would be of benefit in attenuating the deterioration of vessels particularly in a subset of subjects with initial HbA1c > 5.4 and one additional cardiometabolic risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidized LDL has been shown to stimulate the secretion of excess extracellular matrix, MCP-1 and PAI-1 from mesangial cells (92,126,127). These effects may be related to binding of these lipoproteins to VLDL and LDL receptors in mesangial cells (92,126).…”
Section: Role Of Tg-rich Lipoproteinsmentioning
confidence: 99%
“…LDL, and especially oxidised LDL, may increase the levels of several cytokines in renal vasculature and tissues, thus contributing to monocyte infiltration into the mesangial space, mesangial cell hypercellularity, and mesangial extracellular matrix deposition [18][19][20]. Moreover, the increased cytokine production might disturb podocyteendothelial cell communication, causing glomerular endothelial cell dysfunction and leading to microalbuminuria [21].…”
Section: Introductionmentioning
confidence: 99%